Pendampingan Orang Tua Untuk Mendisiplinkan Anak Belajar Selama Masa Pandemi - Nur Hanifah; Alief Budiyono (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
Due to the COVID-19 pandemic, the government has issued a policy regarding home learning (Online/BDR). This makes parental assistance to children in learning disciplines more strategic. Until now, not many have studied research on parental assistance in disciplining children's learning. This research is a descriptive qualitative research. Data were collected in in-depth interview techniques and participatory observation. The data source is the primary source (parents, either father or mother) which is approached purposively, and followed by snowball sampling. The data were further validated by source triangulation technique. The collected data was then analyzed using the Miles & Huberman interactive data analysis technique. The results of the study resulted in 3 models of mentoring in disciplining children to learn in the pandemic era, namely: First, the Oral Model (Inviting children to study, Encouraging children, and Reminding if there are tasks that have not been done). Second, the Action Model (Limiting the use of gadgets, Accompanying and helping/teaching children to learn, Creating a regular study schedule, Learning homework, and training children to be independent and interested in learning), Third, Additional Models (Consultation with teachers, Explaining the Covid-19 situation, and Provide additional tutoring/learning facilities